2017
DOI: 10.15407/ubj89.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen and its fragments in rat brain: a plausible role for astrocytes in angiostatin generation

Abstract: The purpose of the present study was to examine the plasminogen localization and to detect levels of its fragments (angiostatins)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…To our knowledge, no studies on the function of angiostatin in acute ischemic stroke have been performed. However, we have recently discovered angiostatin isoforms in brain tissue of rats and have found that astrocytes are able to constistently produce angiostatins [50]. Our present investigation reveals that citicoline treatment of patients with acute ischemic stroke decreased anti-angiogenic signalling, specifically implicating angiostatin.…”
Section: Dynamics Of Clinical and Laboratory Parameters In Patients Wsupporting
confidence: 49%
“…To our knowledge, no studies on the function of angiostatin in acute ischemic stroke have been performed. However, we have recently discovered angiostatin isoforms in brain tissue of rats and have found that astrocytes are able to constistently produce angiostatins [50]. Our present investigation reveals that citicoline treatment of patients with acute ischemic stroke decreased anti-angiogenic signalling, specifically implicating angiostatin.…”
Section: Dynamics Of Clinical and Laboratory Parameters In Patients Wsupporting
confidence: 49%
“…The initiation of programmed cell death is determined by evaluating the expression of proapoptotic proteins of the caspase family, Bcl family, and the relative content of cytochrome C in the cytosol compared to its mitochondrial pool (Tomiyama et al, 2010;Jemmerson et al, 2005). Given that glial cells provide all the needs of neurons to perform CNS functions, cultures of glial cells are considered adequate models for evaluating the neurotoxic effects of modern pollutants (Hoffman & Kalinich 2020;Tykhomyrov et al, 2017). Thus, the determination of apoptosis induction in an in vitro model of glial cells should reflect molecular and cellular damage that may be the cause of the neurotoxicity of pyrethroids.…”
Section: Introductionmentioning
confidence: 99%